Renal Fluoride excretion in children following topical application of acidulated phosphate fluoride and sodium fluoride (Mustansiria Dental Journal, 2019)
The aim of this study was to demonstrate that if there is an increase in urinary fluoride and creatinine excretion and F/ Cr ratio after application of acidulated phosphate fluoride APF and sodium fluoride NaF fluoridated gel.The sample chosen consisted of 80 children randomly selected, aged 9-11 years old, lived in Baghdad city with non-fluoridated water areas. The children were divided into two groups, the study group which consists of 60 children who received the topical fluoridated gel, the acidulated phosphate fluoride (APF) and the sodium fluoride (NaF).Urinary samples were taken from them before the topical application of dental fluoride gel APF and NaF and 2 hours afterwards. In an age matched control group of 20 children from the same community, who received no treatment, samples were taken at the same way. The urinary excretion of fluoride was analyzed by determining fluoride ion (F-) level and fluoride/ creatinine (F/ Cr) ratio in the urine.  Results showed that the mean F ion before and 2 hours after acidulated phosphate fluoride application APF was (1.74 and 2.36) respectively, this difference was statistically highly significant (p